Percepção da paisagem: o caso dos viadutos de Santa Maria/RS - Silva, Jamile Pereira da (2022)
Perceiving the landscape is an act that many consider automatic and that depends on the cultural and emotional aspects of a certain person and a certain place. Viaducts are urban equipment that has been increasingly used as a traffic strategy in places where there are conflict roads. What has been noticed is that often this equipment construction does not take into account the impact they will have on their surroundings and on the population’s daily life. This work aims to analyze the perception of the landscape of viaducts in Santa Maria/RS. Through a multi-method research it was possible to obtain relevant results for the study, combining observations analysis and online tools to contact users. In the results, it is evident that the population understands that the viaduct fulfills its main function, but most of them end up creating problems that did not exist in the area before. This study is relevant for addressing issues of mobility and landscape, and has the potential to contribute both in the continuity of the research topic and in improvements of urban equipment’s projects in the municipality and its region.